Chemical, microbiological and sensory characteristics of leather blends produced from mango (mangifera indica 'Ogbomoso') and carrot (daucus carota) (2013)
The postharvest losses in fruits and vegetables in developing countries vary between 15-90%. Many organizations are actively promoting the processing of fruits and vegetables to find a solution to the difficulties encountered in storing large quantities of fresh produce without incurring heavy losses. This study evaluated the chemical, microbiological and sensory properties of leather blends produced from ‘Ogbomoso’ mango and carrot. Purees of mango (Mangifera indica ‘Ogbomoso’) and carrot (Daucus carota) were mixed into five ratios of 100:0%, 75:25%, 50:50%, 25:75%, and 0:100%, mango to carrot ratio. Each blend was then oven-dried at 65°C for 10 hours. Moisture content, crude fat, crude protein, crude fibre, carbohydrate content, vitamin A, vitamin C, titratable acidity, and ash content of the leather blends were determined using standard methods. Sensory characteristics using a 9-point hedonic scale and total mould count of the freshly produced leather blends was determined. Subsequently, 75% leather blend was stored for 60 days at refrigeration (4±1°C) and ambient (28±1°C) temperatures. All data obtained were subjected to ANOVA and means separated using Duncan multiple range test. Crude protein, crude fibre, ash, titratable acidity, vitamin C, vitamin A of the leather blends increased with increase in carrot substitution. No detectable microbial growth was found present in the freshly prepared leather blends. The overall acceptability of the leather blends increased with increase in mango substitution. The leather from 100% carrot was the least acceptable. Crude protein, titratable acid, vitamin A, vitamin C, crude fibre, and crude fat of the 75% mango and 25% carrot leather blend decreased at both storage temperatures. However, greater loss was observed in leather blend stored at ambient temperature. Total mould count after 60 days storage ranged from not detectable to 1.3×102 at 4±1°C and 1.5×102 at 28±1°C. From the study, blending of 75% mango and 25% carrot could be a suitable method for extending the shelf life of both fruits.